The role of Pancasila ideology in legitimizing public policies during the COVID-19 pandemic in Indonesia - Supramudyo, Gitadi Tegas; Irianto, Jusuf; Setijaningrum, Erna; Bahar, Adam Amin (Jurnal Sosiologi Dialektika, 2024)
The national ideology is often utilized as a tool to legitimize governmental actions. This study seeks to examine how government elites use the Pancasila ideology to legitimize public policies in the era of the COVID-19 pandemic. Employing a grounded reflective interpretive methodological approach within the framework of postfoundational discourse, this study shows that several controversial policies implemented during the COVID-19 pandemic tended to be bolstered and justified by their alignment with the Pancasila ideology. These endeavors are chiefly undertaken by governmental actors who espouse these policies. Representing the ruling regime, these government actors consistently assert adherence to the fundamental tenets of Pancasila or self-identify as the most "Pancasilaist”. This strategy is the main characteristic of the utilization of Pancasila in legitimizing public policies during the pandemic era. Nonetheless, it is imperative to note that the prevailing political regime tends to interpret the tenets of Pancasila in accordance with their own interests. The results of this study confirm that within the context of policies aimed at managing the COVID-19 pandemic, the resultant measures have tended towards being pro-capitalist, anti-democratic, and even anti-intellectual. Nevertheless, for the ruling regime, these policies are perceived to be congruent with the Pancasila ideology. This study concluded that Pancasila is predominantly employed as a means of legitimizing actions that uphold these values.